BS EN IEC 61300-2-44. Fibre optic interconnecting devices and passive components. Basic test and measurement procedures. Part 2-44. Tests. Flexing of the strain relief of fibre optic devices and components (11th March 2022) - British Standards Institution,
No abstract available